2010
DOI: 10.1016/j.ijid.2010.02.1589
|View full text |Cite
|
Sign up to set email alerts
|

Specific point mutations in the envelope protein of Tick-borne encephalitis virus enhance non-viraemic transmission efficiency in a tick vector

Abstract: Background: December 2007, some cases of dengue hemorrhagic fever were diagnosed in clildren in Rio de Janeiro, Brazil. Along the following months, the has ravaged the state, infecting more than 150,000 people with 232 suspected deaths. 42% of fatal cases were in children. The deaths showed us that the plasma leakage and shock are more common than hemorrhagic phenomena. In many cases, the presence of pleural, pericardial and peritoneal effusions were associated with a severe disease. The emergency rooms in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Specific mutations in the viral envelope protein of TBEV have been found to affect NVT between co-feeding I. ricinus for Siberian and European TBEV strains (Khasnatinov et al, 2010). Furthermore, it has recently been demonstrated that the structural genes of the European TBEV strain Hypr may determine high NVT rates of the virus between co-feeding I. ricinus ticks, whereas the region of the TBEV genome encoding non-structural proteins determines cytotoxicity in cultured mammalian cells (Khasnatinov et al, 2016).…”
Section: Saliva-assisted and Non-viraemic Transmissionmentioning
confidence: 99%
“…Specific mutations in the viral envelope protein of TBEV have been found to affect NVT between co-feeding I. ricinus for Siberian and European TBEV strains (Khasnatinov et al, 2010). Furthermore, it has recently been demonstrated that the structural genes of the European TBEV strain Hypr may determine high NVT rates of the virus between co-feeding I. ricinus ticks, whereas the region of the TBEV genome encoding non-structural proteins determines cytotoxicity in cultured mammalian cells (Khasnatinov et al, 2016).…”
Section: Saliva-assisted and Non-viraemic Transmissionmentioning
confidence: 99%